1996
DOI: 10.1016/s0020-7292(96)02770-1
|View full text |Cite
|
Sign up to set email alerts
|

Serum alpha l‐fucosidase enzyme activity in ovarian and other female genital tract tumors

Abstract: Serum alpha-L-fucosidase enzyme activity can be useful as a tumor marker in diagnosing advanced malignant epithelial ovarian tumors. Its sensitivity and specificity are comparable to CA 125. However, there is a lack of data to support its usefulness in the diagnosis of early stage disease (Stage 1). The cost of doing the test is one-third that of CA 125 and the test can be more widely applied in developing countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 6 publications
0
12
0
Order By: Relevance
“…This has been attributed to variations in the sialic acid content as well as the two different alleles and polymorphisms within the FUC1 gene. The serum ALF activity in normal individuals is reported to be 381U/ml ±10.86 4.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This has been attributed to variations in the sialic acid content as well as the two different alleles and polymorphisms within the FUC1 gene. The serum ALF activity in normal individuals is reported to be 381U/ml ±10.86 4.…”
Section: Introductionmentioning
confidence: 99%
“…A syndrome previously known as leukocyte adhesion deficiency II is now recognised as a generalized metabolic disease caused by severe hypofucosylation of glycoconjugates including selectin ligands 7. Further to this, alterations in levels of ALF have been reported in the plasma and/or serum of patients with endometrial, hepatocellular and colorectal cancer 8,4,9.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, altered expression of ␣-L-fucosidases and corresponding changes in fucosylation levels are seen in many carcinomas (20,21). Accordingly, the presence of human ␣-L-fucosidase in the serum can be used as an early detection marker for several carcinomas (22)(23)(24). Additionally, ␣-Lfucosidases have been used to determine the function of particular L-fucose residues.…”
mentioning
confidence: 99%
“…Besides, many studies on the relationships between the serum form of AFU and other diseases had been reported. The alterations of AFU activity and properties also possess a high clinical value in the diagnosis of colorectal cancer [ 25 ], ovarian cancer [ 26 ], chronic inflammation, and autoimmune disorders [ 27 ]. Moreover, a comprehensive research project that contains 188,077 patients with 64 clinically defined diseases and 9,519 healthy controls showed that serum AFU activities were higher in patients with preeclampsia, liver cancer, hepatitis, psoriasis, and multiple myeloma, while serum AFU activities were the lowest in patients with uremia, azotemia, myeloproliferative disorder, and Alzheimer's disease among the 64 diseases studied [ 28 ].…”
Section: Discussionmentioning
confidence: 99%